COMPARISON OF THE ANTIMICROBIAL EFFECTIVENESS OF GARLIC EXTRACT AND THE ANTIBIOTIC CLINDAMYCIN ON THE GROWTH OF THE BACTERIA PROPIONIBACTERIUM ACNES AND STAPHYLOCOCCUS EPIDERMIDIS - Imam Prabowo; Daniel Natanael Malona; Oktania Sandra Puspita (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
Acne vulgaris is an inflammatory disorder of pilosebaceous glands caused by an increase in sebum production, abnormal follicle keratinization, and colonization of positive gram P. acnes and S. epidermidis bacteria. Clindamycin antibiotic resistance has been reported because it is used to bacteria that cause acne vulgaris. Garlic extract has antimicrobial properties called allicin. This study aimed to determine the in vitro antimicrobial effectiveness of garlic extract in the growth of P. acnes and S. epidermidis. The samples of this study are garlic extract. This study was a true experimental study conducted using disc diffusion method with Mueller Hinton Agar. The zone of inhibition was observed on all groups of P. acnes and S. epidermidis in all tested concentrations with allicin concentration of 256µg/ml showing the widest zone of inhibition. Statistical analysis using the One- Way ANOVA resulted in (p)<0.005. Conclusively, garlic extract was effective in inhibiting the growth of P. acnes and S. epidermidis.